Development of oncolytic viruses for cancer therapy - Noraini Abd Aziz, *; Poh, Chit Laa * (Elsevier, 2021)
Oncolytic virotherapy is a therapeutic approach that uses replication-competent viruses to kill cancers. The ability of oncolytic viruses to selectively replicate in cancer cells leads to direct cell lysis and induction of anticancer immune response. Like other anticancer therapies, oncolytic virotherapy has several limitations such as viral delivery to the target, penetration into the tumor mass, and antiviral immune responses. This review provides an insight into the different characteristics of oncolytic viruses (natural and genetically modified) that contribute to effective applications of oncolytic virotherapy in preclinical and clinical trials, and strategies to overcome the limitations. The potential of oncolytic virotherapy combining with other conventional treatments or cancer immunotherapies involving immune checkpoint inhibitors and CAR-T therapy could form part of future multimodality treatment strategies.